The Relationship between Sleep Disturbance and Tension Type Headache - Mochamad Bahrudin; Indra Setiawan; Noor Alvira Jihad (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Background: Type of Tension The most typical kind of primary headache is a headache. Sleep disturbances are one of the causes of TTH. Further study is necessary to fully comprehend the connection between sleep disruptions and TTH, however, as their interaction is quite complex. Understanding the connection between sleep issues and tension headaches is one of our main objectives. Methods: Use Google Scholar and PubMed to look up papers and books. Criteria for Scopus-indexed international journals in quartiles 1-4 and national journals 1-6 with SINTA accreditation (S1-6) The last 10 years' worth of periodicals and textbooks were used to compile the literature review. The time period utilized, however, is the most recent ten years due to challenges in locating articles. Results: It was determined from various investigations that TTH and sleep problems are related. There is a reciprocal relationship between the two; headaches can lead to sleep problems, and vice versa.Inference: The prevalence of TTH is correlated with sleep problems.